The effect of dietary methionine concentrations on growth performance of juvenile Nile tilapia (Oreochromis niloticus) fed diets with two different digestible energy levels. (4th February 2016) - He, J.Y.; Tian, L.X.; Lemme, A.; Figueiredo‐Silva, C.; Gao, W.; Yang, H.J.; Han, B.; Zeng, S.L.; Liu, Y.J.
Abstract: A growth trial was conducted to examine the effect of dietary digestible energy (DE) content on methionine (Met) utilization and requirement in juvenile Nile tilapia ( Oreochromis niloticus ). Ten iso‐nitrogenous (288 g kg −1 protein) practical diets, with two DE levels (10.9 MJ kg −1 ; 12.4 MJ kg −1 ) and five methionine supplementation levels (0, 1, 2, 4 and 6 g kg −1 ), were hand‐fed twice daily to triplicate groups of Nile tilapia (initial body weight 8.95 ± 0.06 g) for 8 weeks. Weight gain (WG) and specific growth rate (SGR) increased significantly with increasing dietary methionine concentration at the same DE content ( P  <   0.001). At the same dietary methionine level, WG and SGR of fish fed high‐DE diets were significantly higher than that of fish fed low‐DE diets ( P  =   0.0001), although no interaction was found between dietary DE and methionine supplementation. Based on quadratic regression analysis between dietary methionine concentration and weight gain, optimal methionine requirement for maximum growth, expressed as g Met required kg −1 diet (low‐ versus high‐DE diets), increased as diet DE concentration increased (7.34 versus 9.90 g kg −1 diet, respectively; with cysteine 4.70 g kg −1 diet). The results indicated that diet DE content affects methionine utilization and requirement in juvenile Nile tilapia, fish fed high‐DE diets required more methionine for maximum growth.